When Your School is in a ‘Rough’ Neighborhood: What Can Shield Youth from Crime and Delinquency? - Timmer, Anastasiia (American journal of criminal justice, 2024)
Youth spend much of their time socializing and hanging out with friends, as well as engaging in extracurricular activities, in areas surrounding their schools. Additionally, many studies document a criminogenic effect of schools on the surrounding neighborhood. Yet little is known about how the structural characteristics of those areas shape adolescent involvement in criminal and delinquent behavior. Using recent data drawn from surveys of adolescents in three major U.S. cities, the American Community Survey, and the US Census, we analyze (1) the effects of school neighborhood contexts on adolescent crime and (2) the extent to which individual propensity (i.e., moral beliefs and self-control) moderates the effects of the school neighborhood context. We find that concentrated disadvantage and ethnic heterogeneity of the school area impact delinquent behavior only among youth with certain moral beliefs. Our findings highlight the need to identify the conditions under which social context matters and to focus on different types of neighborhoods beyond residential areas.